Electric property measurement of free-standing SrTiO3 nanoparticles assembled by dielectrophoresis. (22nd May 2018) - Budiman, Faisal; Kotooka, Takumi; Horibe, Yoichi; Eguchi, Masanori; Tanaka, Hirofumi
Abstract: Free-standing strontium titanate (SrTiO3 /STO) nanoparticles (NPs) were synthesized by the sol–gel method. X-ray diffractometry revealed that the required minimum annealing temperature to synthesize pure and highly crystalline STO NPs was 500 °C. Moreover, morphological observation by field emission scanning electron microscopy showed that the STO NPs have a spherical structure and their size depended on annealing condition. Electrical properties were measured using a low-temperature probing system. Here, an electrode was fabricated by electron beam lithography and the synthesized STO NPs were aligned at the electrodes by dielectrophoresis. The conductance of a sample was proportional to temperature. Two conduction mechanisms originating from hopping and tunneling appeared in the Arrhenius plot.